P75 Beyond education: maximising the impact of in-situ simulation in intensive care. (3rd November 2019) - Whitehead, Andrew; Glaze, Steffan; Edwards, Alexandra; Navaneetham, Krishna; Jacques, Andrew
Abstract : Introduction: Inter-professional in-situ simulation has been an integral part of the ICU education programme at the Royal Berkshire since 2015. Simulation has become a well-established, routine part of the working of our unit running twice a month. Participants' feedback has always been positive. We aspired to build on this, extend the reach of our simulation programme and seek to maximise its impact on patient safety. We describe how we have used our in-situ simulation to develop organisational learning¹ in our unit and manage latent threats². Method: Our approach to extend the reach of our simulation and maximise impact on patient safety has been multifaceted. In 2016 we started producing a newsletter which is used to disseminate the learning points of the simulation and key features from the debrief to members of the team which have been unable to attend. This is disseminated to all team members via email, and a number of copies are printed and displayed in the department and coffee room. In addition to the inter-professional education aims of the simulation programme, we are using the simulation programme to identify latent threats present on our Intensive Care Unit. Running scenarios in stocked and prepared vacant bed-spaces, and using disposables, equipment and medicines with simulated patients in the same way they are for real patients has enabled the processes and systems in our unit to be tested. Results: In the 24 months from September 2016 to September 2018 we identified 16 latent safety threats through the use of simulation. These ranged from staff knowledge on the use of certain equipment to environment to problems with the setup and layout of the department. We identified six latent threats due to the environment, five due to equipment issues, and five related to knowledge and education. These have been shared with staff via the newsletter, and where possible, rectified after the simulation and where necessary escalated via the hospital incident reporting system. Conclusion: The benefits of in-situ simulation can extend beyond simply educating the participants. We have used our simulation programme to develop our department as 'a learning organisation', educating ourselves about the working dynamics of our department and revealing latent safety threats. This has enabled us to increase staff awareness of these issues via our newsletter and take steps to mitigate them - making our department safer. References: Knight P, MacGloin H, Lane M, Lofton L, Desai A, Haxby E, Burmester M, et al. (2018). Mitigating Latent Threats Identified through an Embedded In Situ Simulation Program and Their Comparison to Patient Safety Incidents: A Retrospective Review. Frontiers in pediatrics, 5, 281. Carroll JS, Edmondson AC. (2002) Leading organisational learning in health care BMJ Quality & Safety2002;11:51-56.